Keabsahan Tindakan Direktorat Jenderal Perbendaharaan dalam Pelaksanaan Subsidi Bunga atau Margin - Ahmad Zaky Mubarok (Jurist-Diction, 2023)
Abstract This article aims to determine and analyze the legitimacy of actions relating to the authority of the Directorate General of Treasury in implementing the Interest or Margin Subsidy. Interest or Margin subsidy is one form of the National Economic Recovery (PEN) program. This type of research uses doctrinal research methods by approaching laws and regulations and legal concepts. Legality has a scope, namely authority, substance and procedure. As one of the scope of validity of government acts. An act of government is invalid if there is a defect in authority, substance and procedure. The Directorate General of Treasury is appointed as the Proxy User of the interest or margin subsidy budget. The Directorate General of Treasury carries out two functions simultaneously, namely the function of chief operational officer and chief financial officer. Keywords: Interest subsidies, legitimacy of government, Directorate General of Treasury.   Abstrak Artikel ini bertujuan untuk mengetahui dan menganalisa keabsahan tindakan berkaitan dengan kewenangan Direktorat Jenderal Perbendaharaan dalam pelaksanaan Subsidi Bunga Atau Margin. Subsidi Bunga Atau Margin merupakan salah satu bentuk program Pemulihan Ekonomi Nasional (PEN). Tipe penelitian dengan metode penelitian doktrinal dengan melakukan pendekatan peraturan perundang-undangan dan konsep-konsep hukum. Keabsahan mempunyai ruang lingkup yaitu wewenang, subtansi dan prosedur. Sebagai salah satu ruang lingkup keabsahan tidnakan pemerintahan. Suatu tindakan pemerintahan tidak sah jika terdapat cacat wewenang, subtansi dan prosedur. Direktorat Jenderal Perbendaharaan ditunjuk sebagai Kuasa Pengguna Anggaran subsidi bunga atau margin. Penunjukan Kuasa Pengguna Anggaran ini merupakan pelaksanaan fungsi Chief Operational Officer Subsidi Bunga atau Margin. Direktorat Jenderal Perbendaharaan juga berperan sebagai Kuasa Bendahara Umum Negara yang merupakan pelaksanaan fungsi Chief Financial Officer. Kata Kunci: Subsidi Bunga, keabsahan tindakan pemerintahan, Direktorat Jenderal Perbendaharaan;